Entrepreneurship Education and Intergenerational Learning in Family Business Sustainability: The Case of Ibu Teti’s Kiosk - Indriati, Dewi Nabila; Marpaung, Sanny Margaretha Br; Nurmiptah, Vina; Syafariyah, Meisya; Fauziyah, Azizah (Journal Corner of Education, Linguistics, and Literature, 2025)
This study focused on how generation gaps affect business sustainability and growth, with special attention to the role of entrepreneurship education and intergenerational learning within the family. The research aims to analyze the challenges of family business sustainability, particularly in dealing with differences in interests between generations in Mrs. Teti's kiosk business. As a family business, the challenges faced are often related to the involvement of different generations who bring diverse priorities, values, goals, and approaches to learning about business practices. Using a qualitative approach, data were collected through interviews with business owners and potential successors to understand their views on business management, succession planning, and strategic decision-making. The research findings show that differences in interests between the first and second generations especially concerning the modernization of business practices while preserving traditional methods create tensions that can threaten the long-term sustainability of the business. From an educational perspective, these tensions reflect gaps in how entrepreneurial knowledge is transmitted: while the first generation relies on tacit knowledge and experiential learning, the second generation emphasizes formal knowledge, digital literacy, and innovative approaches.In addition, challenges related to adapting to market changes, integrating technology, and preparing a structured succession plan also emerge as key factors that need to be addressed so that the business can survive across generations. This study provides insight into how family businesses can manage generational differences by fostering entrepreneurship education within the family—through mentoring, knowledge-sharing, and collaborative learning—to develop strategies that ensure business sustainability amidst evolving family dynamics and business environments.